Digging to America : a novel - Tyler, Anne. (New York : Alfred A. Knopf, 2006)
Two families awaiting the arrival of their adopted infant daughters from Korea meet at the airport. The families lives become interwined after the Donaldsons, a young American couple invite the Yazdan$1 (Bs, Maryam, her son and his Iranian American wife to an arrival party, which becomes an annual event. Maryam, who came to this country thirty-five years earlier, feels her values threatened when she is courted by a newly widowed Donaldson. A penetrating light on the American way as seen from two perspectives, those who are born here and those who are still struggling to fit in.s
Keywords: Iranian American women -- Fiction; Assimilation (Sociology) -- Fiction; Intercountry adoption -- Fiction; Iranian Americans -- Fiction; Women immigrants -- Fiction; Friendship -- Fiction; Widows -- Fiction; Baltimore (Md.) -- Fiction; Psychological fiction; Domestic fiction